Pengaruh Kualitas Pelayanan terhadap Kepuasan Mahasiswa Pengguna Jasa Perpustakaan Pusat Universitas Merdeka Madiun - Indartini, Mintarti (JURNAL EKOMAKS : Jurnal Manajemen, Ekonomi Kreatif dan Bisnis, 2018)
Higher education institutions such as universities in the era of technology and information required to improve services in the field of education by using information technology quickly and precisely, so the college can improve its performance. Especially in terms of services in the academic field and as motivate colleges to transform the structure and strategy of development of educational facilities and prerequisites in order to become a superior higher education institutions, making progress, able to compete and trusted by stackholder.The purpose of this study were (1) To analyze the influence of tangible, reliability, responsiveness, assurance and empathy variable partially on student satisfaction of library service user of Universitas Merdeka Madiun. (2) To analyze the influence of tangible, reliability, responsiveness, assurance and empathy variable simultaneously toward student satisfaction of library service user of Universitas Merdeka Madiun. The result of research show that (1) Tangible partially affect the satisfaction of students of central library user of Universitas Merdeka Madiun. (3) Partial responsiveness affects student satisfaction of library user of University of Merdeka Madiun University (4) Assurance partially has no effect on student satisfaction of library user of University of Merdeka Madiun. (5) Emphaty partially affect student satisfaction of library user of University of Merdeka Madiun and (6) Tangible, reliability, responsiveness, assurance and emphaty simultaneously influence student satisfaction of library user of University of Merdeka Madiun. Keywords: Tangible, Reliability, Responsiveness, Assurance, Emphaty, Satisfaction